2015
DOI: 10.1080/03601234.2015.1018762
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and isotherm analysis of 2,4-dichlorophenoxyl acetic acid adsorption onto soil components under oxic and anoxic conditions

Abstract: 2,4-dichlorophenoxyl acetic acid (2,4-D, pKa = 2.8) is used extensively as a herbicide in agricultural practices. Its sorption behavior on both untreated and soils treated to significantly remove specific components (organic and iron and manganese [Fe-Mn] oxides and hydroxides phases) was investigated under oxic and anoxic conditions. The chemical and structural heterogeneity of the soil components were characterized by elemental analysis and X-ray diffraction (XRD). The coexistence of the various components s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…The treatment not only enhanced the d-spacing from 3.432 in UNTD to 3.581 , 3.553 and 3.494 in S -Mn , S -FeMn and S -OM respectively but also the peaks of isolated samples, indicating that phase transformation occurred on the untreated samples. Similar observations on all the characteristic features of the original and isolated soils in this study were reported in our recent studies [17][18][19][20].…”
Section: Characterization Of Original and Isolated Soilssupporting
confidence: 90%
See 4 more Smart Citations
“…The treatment not only enhanced the d-spacing from 3.432 in UNTD to 3.581 , 3.553 and 3.494 in S -Mn , S -FeMn and S -OM respectively but also the peaks of isolated samples, indicating that phase transformation occurred on the untreated samples. Similar observations on all the characteristic features of the original and isolated soils in this study were reported in our recent studies [17][18][19][20].…”
Section: Characterization Of Original and Isolated Soilssupporting
confidence: 90%
“…In addition to the original untreated soil (UNTD), soil samples were also prepared with three different reagents to extract target components. Details have been published in our recent report on sorption of glyphosate, 2,4,6-TCB, 2,4-D and PFOS [17][18][19][20]. Briefly, 0.1 M NH 2 OHÁHCl and 0.01 M HNO 3 were used for 30 min to remove manganese oxides, and the product is denoted as S -Mn [36].…”
Section: Soil Sampling and Selective Extractionmentioning
confidence: 99%
See 3 more Smart Citations